Water toxicity detection using cell-based hybrid biosensors - Fei, Liu; Voiculescu, Ioana; Nordin, Anis Nurashikin; Fang, Li (2013)
This paper presents a novel cell-based biosensor device that contains a quartz crystal microbalance (QCM), integrated with the electric cell-substrate impedance sensing(ECIS) technique. Bovine aortic endothelial cells (BAECs) are cultivated on the sensors and monitored in parallel by both sensors. When two different sensors monitors the same BAECs monolayer cultures on these sensors the information provided by these sensors is more accurate. Cell culturing microwells were fabricated and glued on this biosensor device for minimizing media and reagent demands and potential automation. The microwells were designed in a manner that can eliminate the fluid shear stress and allow laminar flow for the media and other fluids introduced in the cell-culturing chamber during testing. We demonstrated that BAECS cells could be cultured in these microwells. Resonant frequency and impedance spectroscopy measurements were performed during a time interval. It was demonstrated that this cell- based sensor could be used for toxicity experiments.